The Relationship between Dietary Habits and Type 2 Diabetes for Contribution to Health Promotion: Literature Review - Yolanda Safitri; Tri Krianto (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2024)
Introduction: Type 2 Diabetes Mellitus (T2DM) is a chronic condition largely influenced by dietary habits and eating behaviors. Poor dietary choices, such as high consumption of refined sugars, unhealthy fats, and low intake of fiber, are well-established risk factors for the development of T2DM. The promotion of healthy eating behaviours and active lifestyles is essential to address the increasing prevalence of T2DM and improve public health. Objective: This study aimed to examine the impact of various dietary patterns and specific food intakes on the risk of T2DM, as well as the role of meal timing and dietary quality in influencing blood glucose levels and insulin sensitivity. Method: This research employs a literature review method by analyzing several relevant studies. The articles were sourced from Scopus and Google Scholar, using keywords such as "feeding behavior," "eating behavior," "feeding patterns," "food habits," "dietary habits," and "type 2 Diabetes," "diabetes Type 2," "type 2 diabetes mellitus," "diabetes mellitus type 2," and "T2DM." Result: The results of the article search revealed 13 articles from 2019-2024 that matched the criteria set. The results showed that Eating habits have a significant effect on the risk of developing Type 2 Diabetes Mellitus (T2DM). Poor food choices and irregular eating patterns increase the risk. Conclusion: The paper highlights the significant impact of dietary habits and eating behaviors on the development and progression of Type 2 Diabetes Mellitus. It emphasises the importance of healthy food choices and regular eating patterns in managing blood glucose levels and insulin sensitivity. These insights could contribute to designing an effective health promotion program.